Effect of Atorvastatin on blood ketone levels and glycemic control in patients with type 2 diabetes mellitus: A single arm pilot study. Issue 5 (September 2020) - Baul, Priyanka Basu; Deepak, Arya Desh; Kakkar, Monica; Modi, Sagar
Abstract: Background and aims: Cholesterol and ketone bodies are synthesized in liver from a common precursor acetyl coenzyme A (acetyl-CoA). Statins by inhibiting cholesterol synthesis may lead to accumulation of acetyl-CoA in hepatocytes and its diversion towards ketogenesis. Ketone bodies may act as alternative energy source thus sparing blood glucose and contributing to hyperglycemia. The present study aims to assess the effect of Atorvastatin therapy on blood ketone levels and glycemic control in patients with T2DM. Methods: Study included 24 statin naïve subjects with T2DM. They were prescribed tablet Atorvastatin at dose of 10 mg once daily at bedtime. Ongoing anti-diabetic medications were not changed. Estimation of blood ketones, urine ketones, fasting plasma glucose (FPG), post-prandial plasma glucose (PPG), glycated hemoglobin (HbA1c) and lipid parameters was carried out at baseline and at 3 months after starting Atorvastatin. Results: There was moderate but significant increase in blood ketones (0.16 ± 0.08 mmol/L vs. 0.26 ± 0.07 mmol/L; p-value = 0.0000), FPG (133.8 ± 17.91 mg/dL vs. 143.3 ± 22.99 mg/dL; p-value = 0.0016) and PPG (193.0 ± 36.54 mg/dL vs. 211.0 ± 49.51 mg/dL; p-value = 0.0344) after 3 months of Atorvastatin therapy. This was associated with significant reduction in serum total cholesterol and low density lipoprotein cholesterol. Conclusion: Three months therapy with Atorvastatin at the dose of 10 mg once daily at bedtime in patients with T2DM resulted in moderate rise in blood ketone levels, FPG and PPG in addition to improvement in lipid parameters. Highlights: Atorvastatin is associated with modest elevation in blood ketones in type 2 diabetes mellitus. Rise in blood glucose levels is also observed with Atorvastatin. The present study suggests a plausible mechanism underlying statin-induced hyperglycemia. Ketones may be utilized as alternative fuel in brain and skeletal muscles thus sparing blood glucose.